(untitled) (Bodhi Path, 2025)
The term "Pāli" refers to a collection of sacred texts used by Buddhists. The literature written in the Pāli language primarily addresses religious and philosophical themes. Pāli literature is comprised of a rich assortment of Buddhist texts and scriptures. The most significant part of Buddha’s teachings is known as the "Tipitaka," which many believe contains the original teachings of the Buddha. While scholarly opinions vary regarding the existence of writing in India before the time of Asoka (3rd century B.C.), there is a consensus among historians that the earliest phase of the Buddhist textual tradition was oral. It is believed that both the Tipitaka and its commentary were written down during the reign of Vattagāmanī Abhaya in the first century B.C. This event took place at the Fourth Buddhist Council, where the Pāli Tipitaka was formally recorded for the first time, as it had previously been transmitted orally from generation to generation. Today there is no real peace and happiness in the world. All people are running here and there to bring peace and happiness to society. It shows that there is something lacking in the minds of people. We need the religious principle that can bring peace to individuals and society. Thus, mettā, or ’ loving-kindness’ becomes an essential factor in restoring peace to society. Different interpretations are made in the case of the word mettā according to the context in which it is applicable. Since the word has been arbitrarily used mettā may denote many meanings. When the concept of love is being discussed, scholars may use it differently according to the basic knowledge which they have. Here, the Pāli word ’Mettā’ is strictly used in the sense of Loving-kindness, and not in the sense of ordinary, sensual, emotional, passionate love. In fact, the word ’Love’ has various denotations and connotations in English, according to the contexts in which it is used. My research paper shall be focused on mettā in Pāli Literature. Further, I will also talk about the Braham vihāra in my research paper. The proposed paper will provide a detailed explanation of these points.